2020
DOI: 10.1002/lary.29111
|View full text |Cite
|
Sign up to set email alerts
|

Do Postoperative Oral Corticosteroids Improve Results After Sialendoscopy for Ductal Stenosis?

Abstract: Objectives This study aims to review the effects of short‐ and long‐term oral administration of postoperative corticosteroids in patients undergoing sialendoscopy for the treatment of obstructive sialadenitis due to ductal stenosis. Study Design Prospective comparative study. Methods A prospective observational study was conducted at Manukau Surgical Center in Auckland, New Zealand, where patients undergoing sialendoscopic surgery for recurrent obstructive sialadenitis due to ductal stenoses were reviewed. Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…More high-quality evidence is required in the form of a comparative study or randomized controlled trial, with appropriate long-term follow up. To date, the benefits of oral steroids after sialendoscopy for ductal stenoses have been clearly described in only 1 paper, 24 but the risk versus benefit of oral steroid administration remains as yet undefined, and requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More high-quality evidence is required in the form of a comparative study or randomized controlled trial, with appropriate long-term follow up. To date, the benefits of oral steroids after sialendoscopy for ductal stenoses have been clearly described in only 1 paper, 24 but the risk versus benefit of oral steroid administration remains as yet undefined, and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 study was prospective comparing patients with ductal stenoses that had no steroids after sialendoscopies and those who had postoperative oral steroids for more than 7 days and less than 7 days. 24…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While prednisolone, triamcinolone, and hydrocortisone have all been used topically, there are no studies to date analyzing outcomes of steroid irrigation [2]. One study of 140 adults found that patients with ductal stenoses who were treated with a 1-week course of oral steroids followed by a slow taper were significantly less likely to require repeated sialendoscopy for recurrent symptoms as compared to those who received less than 1 week of postoperative oral steroids [29].…”
Section: Diagnostic and Interventional Sialendoscopymentioning
confidence: 99%